Charting the upstream: An indicator for imported input goods prices - Leif Brubakk; Kristine Aunvåg Matsen; Kristin Mjølnerød; Ørjan Robstad; Elisabeth Werenskiold (Norges Bank, 2024)
This Staff Memo presents an indicator used for monitoring and forecasting inflation at Norges Bank. The indicator is designed to capture international price impulses that impact the input costs of domestic firms. Our analysis indicates that the marked increase in the cost of imported intermediate goods over the last couple of years can account for parts of the rise in Norwegian CPI-inflation in the same period. The results suggest that changes to the price of products at early stages in the production chain can lead to changes in CPI, also making the indicator useful for forecasting.
hdl:11250/3170179
Keywords: 330